2008
DOI: 10.1590/s1807-59322008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of the Superficial Epithelium of Ovaries in Senile Female Rats Following Oral Administration of Conjugated Equine Estrogens

Abstract: Perniconi SE, Simões MJ, Simões RS, Haidar MA, Baracat EC, Soares Junior JM. Proliferation of the superficial epithelium of ovaries in senile female rats following oral administration of conjugated equine estrogens. Clinics. 2008;63:381-8. OBJECTIVE:To evaluate the effect of different concentrations of estrogen on the ovarian superficial epithelium in senile female rats. Design: Fifty female rats at 15 months of age and with irregular estrous cycles were selected and randomly divided into five experimental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(50 reference statements)
2
2
0
Order By: Relevance
“…OSE exhibited an increase in the multilayers of squamous epithelium. Similar findings also reported in other studies (Perniconi et al, 2008;Vuong et al, 2017). Epithelial cells exhibit contact behavior for proper formation of the epithelial monolayer by inhibiting cell proliferation upon contact with neighboring cells.…”
Section: Discussionsupporting
confidence: 91%
“…OSE exhibited an increase in the multilayers of squamous epithelium. Similar findings also reported in other studies (Perniconi et al, 2008;Vuong et al, 2017). Epithelial cells exhibit contact behavior for proper formation of the epithelial monolayer by inhibiting cell proliferation upon contact with neighboring cells.…”
Section: Discussionsupporting
confidence: 91%
“…82,83 Previous studies showed that the administration of high doses of estrogen promoted the excessive proliferation of ovarian epithelium of 12-month-old female rats. 84 Our study reinforces that low doses of ethinylestradiol may lead to thickening of ovarian epithelium. Thus, other studies should be developed to evaluate the effects of low doses of estrogen during prenatal and puberty in the risk of ovarian cancer and other proliferative disorders.…”
supporting
confidence: 87%
“… 18 As the prevalence of the various risk factors for GDM, among which is polycystic ovarian syndrome, is rising worldwide 19 , there is necessary to anticipate the possible complications among these patients. The authors have not noticed any other morbidity risk as family malignant potential 20 , 21 , 22 or rather a frequent pathology in women as endometriosis. 23 , 24 , 25…”
Section: Discussionmentioning
confidence: 68%